Lembaga Pendidikan Muhammadiyah (Telaah Pemikiran K.H. Ahmad Dahlan tentang Pembaruan Pendidikan Islam di Indonesia) - Wahyu Lenggono (Islamadina : Jurnal Pemikiran Islam, 2018)
The thought of Islamic Renewal became a very interesting study in the development of thought in the Islamic world. Moreover, the emergence and renewal movement that occurred in Indonesia provide a new atmosphere that is more advanced in the field of Islamic Education. The purpose of writing this paper is to know the thinking K.H. Ahmad Dahlan on the Renewal of Islamic Education in Indonesia. The method used is qualitative with the approach used is the library reseach where the data obtained through various literasi existing. The results showed that K.H. Ahmad Dahlan is a figure of renewal thinkers in Indonesia who are engaged in education through the organization that formed the Muhammadiyah. K.H. Ahmad Dahlah as a figure of renewal in Indonesia comes with his thoughts to respond to the condition of the people especially in the field of Islamic education is very bad in Indonesia during the Dutch colonial government. See it with the K.H. renewal movement Ahmad Dahlan is struggling to change Education for the better and foremost